Pope Pius XII: From the Diplomacy of Impartiality to the Silence of the Holocaust - Coppa, Frank J. (A journal of church and state, 2013)
Over half a century after the Second World War and the Nazi genocide of the Jews, controversy continues to swirl about the person and policies of Pius XII (pope